A Formal Method for Conceptual Fit Analysis - Olivé, Antoni (Complex Systems Informatics and Modeling Quarterly, 2015)
One criterion that has received little attention in Commercial-off-the-shelf (COTS) systems selection is what we call conceptual fit. The criterion assesses the fit between the conceptual structure of the user requirements and that of a candidate system. In this paper, we evaluate the fit in terms of the existing misfits. We formally define the notion of conceptual misfit and we present a method that determines the conceptual misfits between the user requirements and a set of candidate systems. The method consists of defining a superschema, expressing the user requirements and the implementation of the candidate systems on the basis of that superschema, and the automatic computation of the existing conceptual misfits. The method has been formalized in UML/OCL. We show how our method improves on existing conceptual fit analysis methods for COTS selection.